Development of digital comics for learning Pancasila and civics for second graders - Amanda Rizki Pama Cicilia Putri; Safrul Safrul (Curricula: Journal of Curriculum Development, 2025)
Pancasila and Civic Education in elementary schools often struggle to convey abstract values through conventional, text-heavy methods, resulting in low student engagement. This challenge is amplified by the Kurikulum Merdeka framework, which demands innovative, student-centered learning. This research and development study aimed to design, develop, and evaluate a value-based digital comic to enhance citizenship understanding and critical thinking for second-grade students. Employing the systematic ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the media was developed and subsequently tested with 26 students. Material experts, media experts, and educational practitioners comprehensively validated it. The results demonstrated a high feasibility rating. Furthermore, qualitative observations confirmed that the digital comic not only increased student motivation but also effectively facilitated the comprehension of complex citizenship concepts and stimulated ethical reasoning. The findings imply that systematically designed digital comics are a transformative pedagogical tool, capable of bridging theoretical instruction with practical application, making them a highly effective alternative for revitalizing Citizenship Education in early learning environments.   Abstrak Pendidikan Pancasila dan Kewarganegaraan di sekolah dasar seringkali kesulitan menyampaikan nilai-nilai abstrak melalui metode konvensional yang padat teks, sehingga menyebabkan rendahnya partisipasi peserta didik. Tantangan ini semakin kompleks dengan kerangka Kurikulum Merdeka, yang menuntut pembelajaran inovatif dan berpusat pada peserta didik. Studi penelitian dan pengembangan ini bertujuan untuk merancang, mengembangkan, dan mengevaluasi komik digital berbasis nilai untuk meningkatkan pemahaman kewarganegaraan dan pemikiran kritis pada peserta didik kelas dua. Menggunakan model ADDIE (Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi) secara sistematis, media ini dikembangkan dan diuji dengan 26 peserta didik. Media ini kemudian diverifikasi secara komprehensif oleh ahli materi, ahli media, dan praktisi pendidikan. Hasilnya menunjukkan tingkat kelayakan yang tinggi. Selain itu, pengamatan kualitatif menunjukkan bahwa komik digital tidak hanya meningkatkan motivasi peserta didik, tetapi juga secara efektif memfasilitasi pemahaman konsep kewarganegaraan yang kompleks dan merangsang penalaran etis. Temuan ini menyiratkan bahwa komik digital yang dirancang secara sistematis merupakan alat pedagogis transformatif, mampu menjembatani instruksi teoritis dengan penerapan praktis, menjadikannya alternatif yang sangat efektif untuk menghidupkan kembali Pendidikan Kewarganegaraan di lingkungan pembelajaran awal. Kata kunci: komik digital; media pembelajaran; pendidikan Pancasila dan kewarganegaraan; sekolah dasar